Flexible approach to developing the models for 12th grade technology teaching - Bui Văn Hồng; Nguyen Thị Lưỡng (Journal of Technical Education Science, 2011)
The models used for 12th grade technology teaching include two main areas to display the real devices and the schematics. Students can observe the construction and operation of the device and interact with the models when learning theories, doing practices and experiments. The learning outcomes of the students are very high when they study on this model.